Marley & me [videorecording (DVD)] - Wilson, Owen, 1968-; Aniston, Jennifer; Dane, Eric, 1972-; Turner, Kathleen, 1954-; Arkin, Alan; Gamble, Nathan; Bennett, Haley, 1988-; Grogan, John, 1957- (20th Century Fox Home Entertainment, 2009)
John and Jen are journalists who are a newly married couple. Marley is the adopted puppy that no one wants, a high-strung lab who is virtually untrainable. Marley shreds cushions, destroys floors and walls and most everything in between. Instead of taking him to the pound, they love their dog and he faithfully loves them in return. John and Jen eventually have three children and Jen gives up her career to be a mom. John's career continues to advance as he carves a niche as a local columnist. The family moves from Florida to Pennsylvania. John struggles with his own career direction, but Marley remains the constant. A memoir of Philadelphia Inquirer columnist John Grogan's life with his yellow Labrador retriever.